The influence of mobile phone addiction on academic performance among teenagers - Jamaluddin Abd. Rashid,; Ahlam Abdul Aziz,; Aris Abdul Rahman,; Shahnil Asmar Saaid,; Zaiha Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study aims to identify how addiction to mobile phone usage affects academic performance. Mobile phone addiction has become a deterrent in student learning as teenagers may focus totally on their mobile phones to a point that they become dependent on them. In turn, dependence on mobile phones in their daily lives may affect teen academic performance. This study investigates mobile phone usage among teens and how it impacts their concentration on academic matters. A quantitative approach was undertaken to determine how the level of mobile phone addiction could affect their academic performance. A total of 200 respondents among secondary school students in Shah Alam were selected through purposive sampling. The questionnaire was designed in two sections, which consisted of demographic information and mobile phone usage behaviours that influence academic performance. The results show that the more the students use their mobile phones, the more it will affect their academic performance. In other words, addiction to mobile phones will affect the student’s academic performance. Thus, student attention may divert away from their academics if they have high addiction to their mobile phones. As a result of this study, it has been validated that mobile phones have transformed communication and connectivity among members of the public, students in particular, and that these objects have become indispensable in this contemporary era.